Physical Medicine and Rehabilitation Pocketpedia - Shatzer, M. Matthew; Choi, H. Howard (Demos Medical, 2018)
Pocketpedia is the essential quick reference for medical students, residents, and attending physicians in the field of physical medicine and rehabilitation. Designed for the busy clinician, this pocket-sized compendium is crammed with useful tables, charts, illustrations, and clinical tips and guidelines for effective patient care and restoration of function. Covering core topics in PM&R and field-tested in the clinic and at the bedside over two successful editions, this indispensable resource delivers the information practitioners need on a daily basis. The Third Edition has been reorganized and thoroughly updated to include the latest evidence-based treatment recommendations and protocols.